Pemanfaatan Sistem Presensi Online untuk Peningkatan Kinerja Pegawai Klinik - Muhammad Razi; Tri Suratno; Benedika Ferdian Hutabarat; Dedy Setiawan; Dewi Lestari; Yolla Noverina; Willy Bima Alfajri (Cahaya Pengabdian, 2025)
This community service activity was implemented at Praktek Dokter Pattimura, which has three branches in Jambi City. The main issue faced by the partner was the manual employee attendance system using physical books or unconnected fingerprint devices, leading to slow, inaccurate, and high-risk data loss records, making it difficult for management to monitor employee discipline. This condition increased the administrative burden and hindered the effectiveness of human resource management. The solution offered was the development of a digital attendance application based on web and mobile platforms. This system utilizes face recognition technology for identity verification and GPS integration to ensure attendance can only be done within the clinic area. The system includes a mobile application for daily employee attendance and a web dashboard for owners and administrators to monitor real-time presence data. This solution makes the attendance recording process faster, more accurate, transparent, and integrated, thereby encouraging increased employee discipline and clinic management effectiveness. The implementation was carried out through the Prototype model, including coordination, system development, training, and continuous assistance.